Building Holistic Education: Lessons from Al-Ghazali for the Modern Era - Chusyairi, Kholil (Journal of Modern Islamic Studies and Civilization, 2024)
This study describes al-Ghazali's thoughts on Islamic religious education. Where al-Ghazali's thoughts in the field of education emphasize more that education is a way to bring his servants closer to Allah SWT, with the main goal of obtaining happiness both in this world and in the hereafter and this will be very useful in fast-paced times, in seeking a information, because in this day and age many people are more concerned with high intelligence education with the hope that the smarter a person is, the more successful that person will be in the future. However, society forgets that in life it does not only require high intelligence, but also requires qualified ethics, and this will be obtained by someone by getting closer to the Creator. The method used in this research is library research, the author conducts an assessment of al-Ghazali's thoughts in viewing Islamic education through various related books and journals, which makes it easier for the writer to complete this research.